Clinical pharmacology of modern nootropics and their role in the therapy of kinesia (sickness) - V. V. Kosarev; S. A. Babanov (Медицинский совет, 2013)
Present-day globalization of the world economy, stronger communication in business, science, education and leisure, growth of the population migration (including seasonal) have led to an increase in the incidence of kinesia (sickness). Kinesia is a motion sickness (from Greek kynesis - movement) which occurs when human body is subject to more or less lengthy or variable acceleration . Kinesia is a general term, since it may be caused by any type of movement, even cross-country walk. There are other names for kinesia: travel sickness, sea sickness, air sickness, car sickness and more. It may appear while riding on a merry-go-round or swings, or swinging around in a dance [1–3].